Decoding the future: a bibliometric exploration of blockchain in logistics - Mª Del Valle Fernández Moreno; Juan Miguel Alcántara-Pilar; Marta Tolentino (Financial Innovation)
Abstract This paper presents the results of a bibliometric analysis concerning the application of blockchain technology to logistics. It aims to discern the relational structure among past and current topics, predict emerging trends, and provide a longitudinal perspective on this research domain. Using co-word analysis techniques, we employ SciMAT software to analyze over 800 papers from 2016 to March 2023. The investigation enhances the understanding of blockchain technology, revealing that scientific production in this area revolves around eight primary thematic clusters. Visual representations of the results are provided through longitudinal maps and strategic diagrams, illustrating pivotal themes across the three study periods: blockchain and sustainability. Smart contracts emerge as a focal topic in the final period under consideration.